(untitled) (Scientific journal of the Fergana State University, 2024)
In recent years, the rapidly growing population of Uzbekistan is also increasing the demand for human settlements. The development of settlements is somewhat complicated, especially in parts of the Oasis, which are surrounded by desert. This article provides a Geographical Survey of the urban settlements of the Vabkent District of the Bukhara Oasis. The article presents some suggestions and recommendations on the specific geographical position of urban settlements in the territory, population, history of formation, net of settlements, problems and their solution, and some considerations on the prospects for development.